1998
DOI: 10.1007/s001340050517
|View full text |Cite
|
Sign up to set email alerts
|

Jugular venous oxygen monitoring: a helpful technique in the early diagnosis of a traumatic carotid- cavernous sinus fistula

Abstract: This report describes the early diagnosis of a right traumatic carotid-cavernous sinus fistula (CCSF) in a patient with head injury manifested as an acute increase in right jugular venous oxygen saturation and with no ophthalmic clinical signs. High values of jugular venous oxygen saturation must be cautiously interpreted with the clinical examination and computed tomographic findings to establish an accurate diagnosis of hyperemia with or without a CCSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Results are very encouraging and reproducible, so the measurement of jugular venous oxygen saturation has become almost routine for the management of head injuries [ 4,5]. It has been reported that SjVO 2 catheters have, incidentally, helped in diagnosing carotid‐cavernous fistulae [ 6–9]. To our knowledge, this is the first time that SjVO 2 measurement has been used for the evaluation of successful embolization of a post‐traumatic arterio‐venous fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Results are very encouraging and reproducible, so the measurement of jugular venous oxygen saturation has become almost routine for the management of head injuries [ 4,5]. It has been reported that SjVO 2 catheters have, incidentally, helped in diagnosing carotid‐cavernous fistulae [ 6–9]. To our knowledge, this is the first time that SjVO 2 measurement has been used for the evaluation of successful embolization of a post‐traumatic arterio‐venous fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Results are very encouraging and reproducible, so the measurement of jugular venous oxygen saturation has become almost routine for the management of head injuries [4,5]. It has been reported that SjVO 2 catheters have, incidentally, helped in diagnosing carotidcavernous fistulae [6][7][8][9]. To our knowledge, this is the first time that SjVO 2 measurement has been used for the evaluation of successful embolization of a posttraumatic arterio-venous fistula.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is based on clinical history as well as physical and radiological examinations. The gold-standard diagnostic test is selective digital angiography of the carotid artery, disclosing the size and the fistula outflow, along with brain magnetic resonance imaging (MRI), angio-computed tomographic scanning (angio-CT scan), saturation of the jugular vein bulb, and transcranial Doppler as adjuvant diagnostic tests 3 11 12 13 14 .…”
Section: Introductionmentioning
confidence: 99%